Kontruksi Jaring Insang 2 dan 3 Inci di Kelurahan Kampung Nelayan Kabupaten Tanjung Jabung Barat - Nelwida Nelwida; Lisna Lisna; Ren Fitriadi (Faculty of Science and Technology University Ibrahimy, 2019)
Gill nets is the most dominant fishing gear used by fishermen in Kampung Nelayan Village. Gill nets 2 and 3 inches are widely used by traditional fishermen and modern fishermen because this tool is very practical to catch fish also friendly to the environment. This study aims to determine the construction and friendliness of fishing gear gill nets 2 and 3 inches which include the length of the net, the width of the net, shortening, buoyancy and sinking power. This research was carried out in the Village of Kampung Nelayan, Tungkal Ilir Subdistrict, Tanjung Jabung Barat District in February 2018. The method used in this research was survey method. The data obtained were analyzed using net dimension analysis and descriptive statistical analysis. Based on the results of research on the construction of 2 and 3 inches gill nets consisting of nylon monofilament made from transparent colors. The knot used by the English knot. Top rope, float, and float buoy made from polyethylene (PE) rope and ballast rope made from polypropylene (PP). The sinker made from tin and gill net 3 inch weight based on bracelet-shaped wire.Net shortening value of 2 inch is 51.75% and has a buoyancy of 3.05 kgf and a sinking power of 9.97 kgf. As well as the value of gill shortening 3 inch 50.62% and the buoyancy generated 6.22 kgf and the sinking power of 365.4 kgf. The value of environmental friendliness of 2 and 3 inch nets has a value of 31.25 and 30.75 and is classified as environmentally friendly fishing gear.